Yield losses by frog-eye leaf spot and anthracnose diseases in soybean under different sowing dates in the hills - MITTAL, R.K. (Indian Phytopathology, 2002)
The two foliar diseases, viz., frog-eye leaf spot and anthracnose, together inflicted 23.7 to 32.5 per cent loss (based on the mean of all the years) in grain yield of soybean var. VL Soya 2, under different sowing dates (May 31, June 10 and 20, and July 1) during Kharif 1994 to 1996, at the Research Farm, Hawalbagh of the V.P.K.A.S., Almora. Mean grain yields obtained under protected and unprotected treatments in the four sowing dates, revealed maximum yields in the earliest sowing of May 31 which was gradually reduced by 8.42, 24.27 and 45.53 per cent with delay in sowing by every ten days, respectively.